2016
DOI: 10.1097/ta.0000000000000888
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics, and long-term follow-up of sternoclavicular injuries

Abstract: Epidemiologic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Clinical symptoms of mediastinal compression have been described to occur in up to 25-50 % of patients presenting with posterior sternoclavicular dislocations [4,10]. Most posterior sternoclavicular injuries will require open reduction-internal fixation, although some authors advocate attempting close reduction of all posterior sternoclavicular injuries since up to 40-50 % of these injuries can be reduced by close reduction [2,10,11]. However, closed reduction of a posteriorly displaced sternoclavicular joint should only be performed in the operating room with a vascular surgeon available given the proximity of the great vessels and possibility of vascular injury [15].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Clinical symptoms of mediastinal compression have been described to occur in up to 25-50 % of patients presenting with posterior sternoclavicular dislocations [4,10]. Most posterior sternoclavicular injuries will require open reduction-internal fixation, although some authors advocate attempting close reduction of all posterior sternoclavicular injuries since up to 40-50 % of these injuries can be reduced by close reduction [2,10,11]. However, closed reduction of a posteriorly displaced sternoclavicular joint should only be performed in the operating room with a vascular surgeon available given the proximity of the great vessels and possibility of vascular injury [15].…”
Section: Discussionmentioning
confidence: 97%
“…The most common mechanism of sternoclavicular joint injury is a direct blow to the shoulder, either from a fall or during sports-related activities. Sternoclavicular injuries can occur at any age but are most common in young adults (average age 29-39 years) with a slight male predilection [2,10,11]. Typically, injuries to the sternoclavicular joint involve a varying degree of injury to the joint capsule ranging from mild capsular stretching to complete disruption.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 3 Dislocations of the sternoclavicular joint comprise 1% of all joint dislocations, and 3% of those in the upper limb. 17 Boesmueller et al 18 found that the incidence of SCJ injuries was 0.9% in all shoulder-girdle lesions and 1.1% in all dislocations. Young, active males are more likely to present with this injury after high-energy trauma.…”
Section: Traumatic Injuries To the Sternoclavicular Jointmentioning
confidence: 98%